A Major Misunderstanding of Minors' Contracts? Enforcement and Restitution Under the Minors' Contracts Act 1969 - Gilbert, James (Victoria University of Wellington Law Review, 2009)
The Minors Contracts Act 1969 divides minors' contracts into two categories – those which are presumptively enforceable against the minor in the absence of unconscionability or oppression, and those which are presumptively unenforceable with an allowance for the exercise of judicial discretion to order remedies of enforcement, compensation or restitution depending on the fairness and reasonableness of the contract. This article focuses on judicial interpretation and application of the law with respect to the latter category, particularly in the case of Wine Country Credit Union v Rayner. It argues that the decision in Rayner to deny the possibility of a restitutionary or compensatory order in favour of the plaintiff lender was incorrect and contrary to parliamentary intention, and that reform of the law relating to minors' contracts is necessary to avoid a repeat of those errors.